Benzoxazine compounds and their uses

A benzoxazine compound derived from polyethylene glycol-modified lignin addresses solubility and meltability issues, enabling improved heat resistance and flexibility, suitable for applications like prepreg formation and casting.

JP7619551B1Active Publication Date: 2025-01-22SHIKOKU CHEM CORP +2

Patent Information

Application Number
JP2024011312
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-01-29
Publication Date
2025-01-22
Estimated Expiration
2044-01-29

AI Technical Summary

Technical Problem

Benzoxazine resins face limitations in applications requiring high heat resistance due to their brittleness and hardness, and conventional modifications, such as those using lignin and polyethylene glycol, suffer from low solubility and meltability, making them unsuitable for processes like prepreg formation.

Method used

A benzoxazine compound is developed using a novolak-type phenolic resin derived from polyethylene glycol-modified lignin, which enhances solubility and meltability, allowing for easier processing and integration with other resins, and a resin composition with improved heat resistance, strength, and flexibility.

Benefits of technology

The resulting benzoxazine compound exhibits excellent solubility and meltability, enabling applications like prepreg formation and casting, with cured products showing high heat resistance, strength, and flexibility, and a lower tensile modulus.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007619551000005
    Figure 0007619551000005
  • Figure 0007619551000001
    Figure 0007619551000001
  • Figure 0007619551000002
    Figure 0007619551000002
Patent Text Reader

Abstract

The present invention provides a benzoxazine compound made from polyethylene glycol-modified lignin, a resin composition containing the benzoxazine compound, and a cured resin product thereof. Specifically, the present invention provides a benzoxazine compound having a lignin skeleton that is soluble or meltable in an organic solvent, and a method for producing the same. The present invention also provides a resin composition containing the benzoxazine compound that provides a cured product having excellent heat resistance, high strength, and low tensile modulus, and a cured product thereof. [Solution] The present invention relates to a benzoxazine compound containing a reaction product of a novolac-type phenolic resin derived from lignin modified with polyethylene glycol, an amine compound, and an aldehyde compound, a resin composition containing the benzoxazine compound, a cured product of the resin composition, a composite (prepreg, etc.) containing the resin composition and a substrate, the cured product of the composite, and a method for producing the benzoxazine compound.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a benzoxazine compound and its use. [Background technology]

[0002] Benzoxazine compounds have been studied for a long time (for example, Patent Document 1), and these substances are synthesized by reacting a phenol compound, an amine compound, and a formaldehyde compound (see reaction formula (1)). [ka] Benzoxazine compounds (monomers) undergo ring-opening polymerization (hardening) when heated to produce benzoxazine resins (polymers), and are therefore attracting attention as a new type of phenolic resin that can replace conventional phenolic resins.

[0003] Although benzoxazine resins have excellent mechanical properties, their hardness and brittleness limit their applicable applications. Although benzoxazine resins have better heat resistance than epoxy resins and phenolic resins, they are not sufficient for applications requiring strict heat resistance, such as power semiconductors and automotive applications.

[0004] Meanwhile, a new benzoxazine compound has been reported that is made from lignin, a plant-derived component (Patent Document 2). In addition to the lignin, lignin modified with polyethylene glycol (PEG) (Patent Document 3) and novolak-type phenolic resins having excellent heat resistance and flexibility, which are made from the PEG-modified lignin, phenols, and aldehydes (Patent Document 4), have been reported. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Publication No. 49-47378 [Patent Document 2] JP 2013-53205 A [Patent Document 3] JP 2017-197517 A [Patent Document 4] JP 2021-123716 A Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide a benzoxazine compound made from polyethylene glycol (hereinafter, sometimes abbreviated as "PEG")-modified lignin, a resin composition containing the benzoxazine compound, and a cured resin thereof.

[0007] Specifically, the present invention aims to provide a benzoxazine compound having a lignin skeleton that is soluble or meltable in an organic solvent, and a method for producing the same, and a resin composition containing the benzoxazine compound that gives a cured product having excellent heat resistance, high strength, and low tensile modulus, and a cured product thereof. [Means for solving the problem]

[0008] The present inventors have confirmed that the benzoxazine compound made from modified lignin described in Patent Document 2 has extremely low solubility and meltability in solvents and resins, making it difficult to apply it to applications such as forming prepregs. The present inventors have conducted intensive research to solve this problem, and as a result have found that a benzoxazine compound made from a novolac-type phenolic resin derived from PEG-modified lignin has excellent solubility and meltability in solvents and resins. In addition, the present inventors have found that a cured product of a resin composition containing the benzoxazine compound has high heat resistance (high glass transition temperature) and also has high strength (high tensile strength) and elongation (low tensile modulus) compared to a cured product of a resin composition containing a conventional benzoxazine compound. Based on this knowledge, the present inventors have conducted further research and have completed the present invention.

[0009] That is, the present invention includes the following aspects. [1] A benzoxazine compound comprising a reaction product of a novolac-type phenolic resin derived from lignin modified with polyethylene glycol, an amine compound, and an aldehyde compound. [2] The benzoxazine compound according to [1], wherein the novolac phenolic resin is obtained by reacting lignin modified with polyethylene glycol, a phenolic resin, and an aldehyde compound. [3] A resin composition containing the benzoxazine compound according to [1] or [2]. [4] A cured product of the resin composition described in [3]. [5] A composite comprising the resin composition according to [3] and a substrate. [6] A prepreg comprising the resin composition according to [3] and a substrate. [7] A cured product of the composite according to [5] or the prepreg according to [6]. [8] A method for producing a benzoxazine compound, comprising the steps of: (1) a step of reacting lignin modified with polyethylene glycol, a phenolic resin, and an aldehyde compound to obtain a novolac-type phenolic resin; and (2) A step of reacting the novolak-type phenolic resin obtained in the above (1), an amine compound, and an aldehyde compound to obtain a benzoxazine compound. A manufacturing method comprising: Effect of the Invention

[0010] The benzoxazine compound having a lignin skeleton of the present invention has excellent solubility in organic solvents and is meltable. Since the benzoxazine compound is meltable, it can be melt-mixed with other resins. Therefore, it can be suitably used for applications such as the formation of prepregs and casting processes. In addition, since the benzoxazine compound is meltable, it can be melt-mixed with other resins. The cured product obtained by curing the resin composition containing the benzoxazine compound having a lignin skeleton of the present invention has the characteristics of excellent heat resistance (high glass transition temperature (Tg)), excellent strength (high tensile strength), and easy elongation (relatively small tensile modulus). The curing reaction of the benzoxazine compound having a lignin skeleton of the present invention proceeds at a relatively low temperature. [Brief description of the drawings]

[0011] [Figure 1] 1 is an IR spectrum chart of the black solid obtained in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] 1. Benzoxazine compounds The benzoxazine compound of the present invention is characterized by containing a reaction product of (1) a novolac-type phenolic resin derived from lignin modified with polyethylene glycol (PEG), (2) an amine compound, and (3) an aldehyde compound.

[0013] (1) Novolac-type phenolic resin derived from lignin modified with PEG The novolac-type phenolic resin derived from lignin modified with PEG contains a reaction product obtained from lignin modified with PEG (hereinafter also referred to as "PEG-modified lignin"), a phenolic compound, and an aldehyde compound. Usually, it can be produced by reacting PEG-modified lignin, a phenolic compound, and an aldehyde compound under an acid catalyst. Specifically, it can be produced according to or in accordance with Patent Document 4 (JP Patent Publication 2021-123716). For example, it is as follows.

[0014] (PEG-modified lignin) In the PEG-modified lignin, which is a raw material for the novolac-type phenolic resin derived from the PEG-modified lignin, the polyethylene glycol (PEG) is appropriately selected depending on the physical properties required for the benzoxazine compound of the present invention.

[0015] From the viewpoint of achieving both high tensile strength and low tensile modulus in the benzoxazine compound of the present invention, the number average molecular weight of polyethylene glycol is, for example, 100 or more, preferably 200 or more, more preferably 300 or more, and even more preferably 400 or more, and for example, 1000 or less, preferably 900 or less, more preferably 800 or less, and even more preferably 600 or less. The number average molecular weight can be determined as a polyethylene glycol-equivalent molecular weight by a known gel permeation chromatography method.

[0016] In PEG-modified lignin, lignin is a polymeric phenolic compound consisting of a basic skeleton such as guaiacyl lignin (G type), syringyl lignin (S type), and p-hydroxyphenyl lignin (H type), and is found in plants as a natural product (natural lignin).

[0017] Known examples of natural lignin extracted industrially include soda lignin, sulfite lignin, and kraft lignin, which are contained in the waste liquid (black liquor) discharged when pulp is produced from raw plant material (lignocellulose) by the soda process, sulfite process, kraft process, or other methods.

[0018] Specific examples of lignin include woody plant-derived lignin and herbaceous plant-derived lignin. Examples of woody plant-derived lignin include coniferous lignin contained in coniferous trees (e.g., cedar, etc.) and broadleaf lignin contained in broadleaf trees. Woody plant-derived lignin does not contain an H-type basic skeleton. More specifically, among woody plant-derived lignins, coniferous lignin does not contain an S-type basic skeleton and has a G-type basic skeleton. Moreover, broadleaf lignin has a G-type basic skeleton and an S-type basic skeleton.

[0019] Examples of lignin derived from herbaceous plants include rice lignin contained in grasses (wheat straw, rice straw, corn, bamboo, etc.). Lignin derived from herbaceous plants has all of the basic skeletons of H-type, G-type, and S-type. These lignins can be used alone or in combination of two or more types.

[0020] From the viewpoint of homogeneity of the PEG-modified lignin, the lignin is preferably a woody plant-derived lignin that does not contain an H-type basic skeleton, more preferably a coniferous lignin that does not contain an S-type basic skeleton and has a G-type basic skeleton, and particularly preferably a coniferous lignin derived from cedar.

[0021] The PEG-modified lignin is not particularly limited, but can be produced, for example, in accordance with the method described in Patent Document 3 (JP 2017-197517 A).

[0022] More specifically, for example, a plant material (lignocellulose) serving as the raw material for lignin can be solvolyzed with polyethylene glycol to obtain PEG-modified lignin.

[0023] The solvolysis method is not particularly limited, but for example, a plant material serving as a raw material for lignin, polyethylene glycol, and an inorganic acid (e.g., hydrochloric acid, sulfuric acid, etc.) as an acid catalyst are mixed and reacted.

[0024] The mixing ratio of polyethylene glycol per 100 parts by mass of the plant material that is the raw material for lignin is, for example, 200 parts by mass or more, preferably 300 parts by mass or more, and for example, 1,000 parts by mass or less, preferably 600 parts by mass or less.

[0025] The mixing ratio of the inorganic acid is, for example, 0.1 part by mass or more, preferably 0.2 part by mass or more, and for example, 2 parts by mass or less, preferably 1 part by mass or less, per 100 parts by mass of polyethylene glycol (100% conversion).

[0026] The reaction conditions are as follows: under normal pressure, the reaction temperature is, for example, 120° C. or more, preferably 130° C. or more, and for example, 180° C. or less, preferably 150° C. or less, and the reaction time is, for example, 60 minutes or more, and for example, 240 minutes or less, preferably 120 minutes or less.

[0027] After the reaction is completed, a known alkali (eg, ammonia, sodium hydroxide, etc.) is added in an appropriate ratio to adjust the pH, and the PEG-modified lignin is extracted into the solution.

[0028] The adjusted pH is, for example, 8 or more, preferably 10 or more, more preferably 10.5 or more, and for example, 14 or less.

[0029] By such a method, pulp is obtained as a solid component, and PEG-modified lignin is obtained as a solution component (pulp waste liquor).

[0030] Next, in this method, the solid component (pulp) is separated from the reaction product by a known separation method such as filtration, pressing, or centrifugation, and the solution component (pulp waste liquor) is recovered.

[0031] Furthermore, in this method, if necessary, the solid component (pulp) can be washed and the solution (PEG-modified lignin) impregnated into the solid component can be recovered.

[0032] The method then involves adding an inorganic acid (eg, hydrochloric acid, sulfuric acid, etc.) and adjusting the pH to precipitate and cause the PEG-modified lignin to precipitate.

[0033] The pH after adjustment is, for example, 1.5 or more, and for example, 5 or less, preferably 3 or less, and more preferably 2 or less.

[0034] This allows the PEG-modified lignin to precipitate, and the resulting precipitate can be collected by a known method such as filtration, pressing, or centrifugation to obtain the PEG-modified lignin as a solid content.

[0035] (Phenol compounds) The phenolic compounds that are the raw materials for the novolac-type phenolic resin derived from PEG-modified lignin are phenol and its derivatives (phenol-modified products), and examples of such compounds include phenol, as well as difunctional phenol derivatives such as o-cresol, p-cresol, p-tert-butylphenol, p-phenylphenol, p-cumylphenol, p-nonylphenol, 2,4- or 2,6-xylenol, trifunctional phenol derivatives such as m-cresol, resorcinol, 3,5-xylenol, and tetrafunctional phenol derivatives such as bisphenol A and dihydroxydiphenylmethane. In addition, examples of phenol derivatives include halogenated phenol compounds substituted with halogens such as chlorine and bromine. These phenol compounds can be used alone or in combination of two or more. When a phenol derivative (phenol modified product) is used, the timing of phenol modification is not particularly limited, and it may be before, after, or simultaneously with the reaction of the PEG-modified lignin with the phenol compound and the aldehyde compound.

[0036] As the phenol compound, preferably, phenol is used.

[0037] (aldehyde compounds) Aldehyde compounds that are raw materials for novolac-type phenolic resins derived from PEG-modified lignin include, for example, formaldehyde, paraformaldehyde, acetaldehyde, propionaldehyde, butylaldehyde (n-butylaldehyde, isobutylaldehyde), furfural, glyoxal, benzaldehyde, trioxane, and tetraoxane. In addition, a part of the aldehyde may be substituted with furfuryl alcohol or the like. These aldehyde compounds can be used alone or in combination of two or more kinds.

[0038] As the aldehyde compound, preferably, formaldehyde and paraformaldehyde can be mentioned.Also, the aldehyde compound can be used, for example, as an aqueous solution.In such a case, the concentration of the aldehyde compound is, for example, 10% by mass or more, preferably 20% by mass or more, and, for example, 99% by mass or less, preferably 95% by mass or less.

[0039] In addition to the aldehyde compound, a ketone compound can also be blended. Examples of the ketone compound include acetone, methyl ethyl ketone, diethyl ketone, acetophenone, and diphenyl ketone. These ketone compounds can be used alone or in combination of two or more kinds.

[0040] When a ketone compound is blended, the blending ratio of the ketone compound, based on the solid content, per 100 parts by mass of the aldehyde compound is, for example, 0.01 parts by mass or more, preferably 1 part by mass or more, and for example, 200 parts by mass or less, preferably 100 parts by mass or less.

[0041] (reaction) To react the PEG-modified lignin with the phenolic compound and the aldehyde compound (and the ketone compound, which is added as necessary, the same applies below), the above-mentioned components (PEG-modified lignin, the phenolic compound, the aldehyde compound, etc.) are mixed and heated. This reaction can also be carried out with the addition of an acid catalyst.

[0042] In this reaction, the mixing ratio of the phenol compound is, for example, 30 parts by mass or more, preferably 50 parts by mass or more, and more preferably 100 parts by mass or more, relative to 100 parts by mass of the PEG-modified lignin, and for example, 1,000 parts by mass or less, preferably 500 parts by mass or less, and more preferably 350 parts by mass or less.

[0043] In addition, from the viewpoint of improving heat resistance, the blending ratio of the phenol compound is preferably 200 parts by mass or more, more preferably 250 parts by mass or more, and preferably 1,000 parts by mass or less, more preferably 500 parts by mass or less, per 100 parts by mass of the PEG-modified lignin.

[0044] The mixing ratio of the aldehyde compound relative to 100 parts by mass of the phenol compound is, for example, 5 parts by mass or more, preferably 10 parts by mass or more, and for example, 35 parts by mass or less, preferably 30 parts by mass or less. The mixing ratio of the aldehyde compound relative to 100 parts by mass of the PEG-modified lignin is, for example, 1.5 parts by mass or more, preferably 3 parts by mass or more, and for example, 350 parts by mass or less, preferably 300 parts by mass or less.

[0045] In this reaction, an acid catalyst can be added. The above components can be reacted in the presence of an acid catalyst. Examples of the acid catalyst include organic acids and inorganic acids.

[0046] Examples of organic acids include sulfonic acid compounds such as methanesulfonic acid, p-toluenesulfonic acid, dodecylbenzenesulfonic acid, cumenesulfonic acid, dinonylnaphthalene monosulfonic acid, and dinonylnaphthalenedisulfonic acid, phosphoric acid esters having an alkyl group having 1 to 18 carbon atoms such as trimethyl phosphate, triethyl phosphate, monobutyl phosphate, dibutyl phosphate, tributyl phosphate, and trioctyl phosphate, and formic acid, acetic acid, and oxalic acid. Examples of inorganic acids include phosphoric acid, hydrochloric acid, sulfuric acid, and nitric acid. These acid catalysts can be used alone or in combination of two or more kinds.

[0047] As the acid catalyst, preferably, an organic acid is used, and more preferably, oxalic acid is used.

[0048] The mixing ratio of the acid catalyst relative to 100 parts by mass of the phenol compound is, for example, 0.1 parts by mass or more, preferably 0.3 parts by mass or more, and for example, 10 parts by mass or less, preferably 5 parts by mass or less.

[0049] The timing of adding the acid catalyst is not particularly limited, and the acid catalyst may be added in advance to at least one of the PEG-modified lignin, the phenol compound, and the aldehyde compound, or may be added simultaneously when the PEG-modified lignin, the phenol compound, and the aldehyde compound are mixed, or may be added after the PEG-modified lignin, the phenol compound, and the aldehyde compound are mixed.

[0050] The reaction conditions are as follows: under atmospheric pressure, the reaction temperature is, for example, 50° C. or more, preferably 80° C. or more, and for example, 200° C. or less, preferably 180° C. or less, and the reaction time is, for example, 1 hour or more, preferably 2 hours or more, and for example, 20 hours or less, preferably 15 hours or less.

[0051] As a result, a novolac-type phenolic resin is obtained as a reaction product of the PEG-modified lignin, the phenolic compound, and the aldehyde compound. More specifically, a novolac-type phenolic resin is obtained by the reaction of the phenolic compound with the aldehyde compound in the presence of an acid catalyst, and the novolac-type phenolic resin is modified by the PEG-modified lignin.

[0052] That is, a novolac-type phenolic resin derived from PEG-modified lignin is obtained.

[0053] In the production of a novolak-type phenolic resin derived from a PEG-modified lignin, unreacted raw materials (unreacted phenolic compounds, etc.) and acid catalyst can be removed, if necessary, by a known method such as distillation.

[0054] The novolac-type phenolic resin derived from the thus obtained PEG-modified lignin contains a reaction product obtained by reacting lignin modified with polyethylene glycol, a phenolic compound, and an aldehyde compound in the presence of an acid catalyst.

[0055] (2) Amine compounds Examples of the amine compound include primary amines.Specific examples of the amine compound include alkyl monoamines or alkenyl monoamines such as methylamine, ethylamine, n-propylamine, n-butylamine, n-dodecylamine, n-nonylamine, cyclopentylamine, cyclohexylamine, and allylamine; and aromatic monoamines such as aniline, p-cyanoaniline, p-bromoaniline, o-toluidine, m-toluidine, p-toluidine, 2,4-xylidine, 2,5-xylidine, 3,4-xylidine, α-naphthylamine, β-naphthylamine, and 3-aminophenylacetylene.

[0056] In addition, benzylamine, 2-aminobenzylamine, 1,3-diaminopropane, 1,4-diaminobutane, 1,10-diaminodecane, 2,7-diaminofluorene, 1,4-diaminocyclohexane, 9,10-diaminophenanthrene, 1,4-diaminopiperazine, p-phenylenediamine, 4,4'-diaminobenzophenone, 4,4'-diaminodiphenylsulfone, 4,4'-diaminodiphenylmethane, 4,4'-diaminobiphenyl, 4,4'-oxydianiline, fluorenetetraamine, tetraaminediphenylether, melamine, and the like can also be used. Among these, aniline, methylamine, etc. are preferred, and aniline is more preferred. Aniline has a phenyl group in the molecule, and the phenyl group further improves the heat resistance of the molded article.

[0057] (3) Aldehyde compounds The aldehyde compound is not particularly limited. For example, formaldehyde, paraformaldehyde, acetaldehyde, propionaldehyde, butylaldehyde (n-butylaldehyde, isobutylaldehyde), furfural, glyoxal, benzaldehyde, trioxane, tetraoxane, etc. may be mentioned. In addition, a part of the aldehyde may be substituted with furfuryl alcohol, etc. These aldehyde compounds may be used alone or in combination of two or more kinds.

[0058] A preferred example is a formaldehyde compound. Examples of formaldehyde compounds include formalin, which is an aqueous solution of formaldehyde, and paraformaldehyde and trioxane, which are polymers thereof. The state of the aldehyde compound used is not limited, and may be solid or liquid. In particular, paraformaldehyde is preferred because it is easy to handle since it is a solid (powder) at room temperature.

[0059] (4) Manufacturing method The benzoxazine compound of the present invention can be produced by reacting components including (1) a novolac-type phenolic resin derived from PEG-modified lignin, (2) an amine compound, and (3) an aldehyde compound.

[0060] The benzoxazine ring is formed at the phenol skeleton in the novolac phenolic resin molecule derived from PEG-modified lignin. For example, by mixing and reacting the above components, a cyclization reaction proceeds at the phenol skeleton to form a benzoxazine ring.

[0061] The molar ratio of the novolac-type phenolic resin derived from the PEG-modified lignin, the amine compound, and the aldehyde compound is theoretically required to form a benzoxazine ring. For example, when each component molecule contains one functional group, the molar ratio of the novolac-type phenolic resin derived from the PEG-modified lignin, the amine compound, and the aldehyde compound is 1:1:2.

[0062] The amine compound and the aldehyde compound can be used in an appropriate ratio depending on the degree of modification of the novolac type phenolic resin derived from the PEG-modified lignin. For example, the amine compound is 0.5 to 30 moles, preferably 0.8 to 20 moles, more preferably 1 to 10 moles, and the aldehyde compound is 1 to 40 moles, preferably 1.2 to 20 moles, more preferably 1.5 to 15 moles, relative to 1 mole of the phenolic hydroxyl group equivalent of the novolac type phenolic resin derived from the PEG-modified lignin.

[0063] In this reaction, an acid catalyst can be added. That is, the above-mentioned components can be reacted in the presence of an acid catalyst. Examples of the acid catalyst include organic acids and inorganic acids.

[0064] Examples of organic acids include sulfonic acid compounds such as methanesulfonic acid, p-toluenesulfonic acid, dodecylbenzenesulfonic acid, cumenesulfonic acid, dinonylnaphthalene monosulfonic acid, and dinonylnaphthalenedisulfonic acid, phosphoric acid esters having an alkyl group having 1 to 18 carbon atoms such as trimethyl phosphate, triethyl phosphate, monobutyl phosphate, dibutyl phosphate, tributyl phosphate, and trioctyl phosphate, and formic acid, acetic acid, and oxalic acid. Examples of inorganic acids include phosphoric acid, hydrochloric acid, sulfuric acid, and nitric acid. These acid catalysts can be used alone or in combination of two or more kinds.

[0065] As the acid catalyst, preferably, an organic acid is used, and more preferably, oxalic acid is used.

[0066] The mixing ratio of the acid catalyst relative to 100 parts by mass of the phenol compound is, for example, 0.1 parts by mass or more, preferably 0.3 parts by mass or more, and for example, 10 parts by mass or less, preferably 5 parts by mass or less.

[0067] The reaction temperature is preferably about 50 to 200° C., more preferably about 100 to 150° C. The reaction time is preferably about 5 minutes to 6 hours, more preferably about 20 minutes to 3 hours.

[0068] The benzoxazine compound produced as described above has superior solubility in solvents and superior melting property compared to benzoxazine compounds based on herbaceous lignin, and also cures faster than conventional benzoxazine compounds, and the cured product has superior heat resistance, strength and flexibility.

[0069] 3. Uses of benzoxazine compounds The present invention further provides a resin composition containing the benzoxazine compound produced above, a cured product thereof, a composite (prepreg, etc.) containing the resin composition and a substrate, and a cured product of the composite. The following is a detailed description.

[0070] The resin composition of the present invention contains the above-mentioned benzoxazine compound, and may further contain additives, such as toughening agents, catalysts, reinforcing agents, fillers, adhesion promoters, flame retardants, thixotropic agents, etc., as necessary. The additives may be used alone or in combination of two or more kinds. The content of the additives may be appropriately set according to the purpose and application, within a range that does not impair the excellent effects of the present invention.

[0071] The resin composition of the present invention may contain other resins as necessary. Examples of other resins include thermosetting resins and thermoplastic resins. Examples of thermosetting resins include epoxy resins, phenolic resins, bismaleimide resins, polyimide resins, silicon resins, melamine resins, urea resins, unsaturated polyester resins, alkyd resins, furan resins, and polyurethane resins. Examples of thermoplastic resins include thermoplastic epoxy resins and thermoplastic polyimide resins.

[0072] The resin composition of the present invention contains a benzoxazine compound as a main component, and may contain other resins (such as thermosetting resins and thermoplastic resins), additives, and the like as secondary components, as necessary.

[0073] In the present invention, the resin composition containing a benzoxazine compound includes both the benzoxazine compound and a mixture containing the benzoxazine compound and other components (additives, other resins, etc.).

[0074] The content of the benzoxazine compound in the resin composition of the present invention is, for example, 1 to 100 mass %, preferably 1 to 90 mass %, more preferably 3 to 85 mass %, and particularly preferably 5 to 80 mass %.

[0075] From the viewpoint of being able to knead with other resins, the minimum melt viscosity (complex viscosity) of the benzoxazine compound and resin composition of the present invention is preferably 0.1 to 10,000 (Pa s) at 100 to 160°C, more preferably 0.1 to 1,000 (Pa s), and particularly preferably 1 to 500 (Pa s).

[0076] In this specification, the minimum melt viscosity (complex viscosity) is specified by the following method: the measurement is performed using a 25 mm diameter parallel plate rheometer (MCR300, manufactured by Anton Paar Japan) under conditions of a gap of 1 mm, a frequency of 1 Hz, a strain of 0.5%, a heating rate of 2°C / min, and a temperature range of 100°C to 180°C, and the minimum melt viscosity (Pa s) is obtained from the obtained viscoelastic curve.

[0077] When the resin composition of the present invention contains additives and / or other resins, the benzoxazine compound and the additives and / or other resins can be mixed (kneaded) by a known method.

[0078] The kneading method is not particularly limited, and for example, known kneaders such as a single screw extruder, a multi-screw extruder, a roll kneader, a kneader, a Henschel mixer, and a Banbury mixer can be used. As kneading conditions, the kneading temperature is, for example, 80° C. or more, preferably 90° C. or more, more preferably 100° C. or more, and 180° C. or less, preferably 170° C. or less, more preferably 160° C. or less. In addition, the kneading time is, for example, 3 minutes or more, preferably 5 minutes or more, and for example, 30 minutes or less, preferably 20 minutes or less. Thereby, a resin composition containing a benzoxazine compound and an additive and / or other resin is obtained.

[0079] The cured product of the resin composition of the present invention can be obtained by curing the above-mentioned resin composition. The curing of the resin composition can be carried out, for example, at 100 to 200° C. for 1 minute to 8 hours.

[0080] The glass transition temperature of the obtained cured product is preferably at least 200° C., more preferably at least 215° C., and particularly preferably at least 230° C. In this specification, the glass transition temperature (Tg) is a value measured from the peak temperature of the loss tangent (tan δ) obtained from a dynamic viscoelasticity test.

[0081] The present invention provides a composite comprising the resin composition of the present invention and a substrate. The composite typically includes a prepreg comprising the resin composition and a substrate. The prepreg of the present invention is usually a composite in which a substrate is impregnated with a resin composition. The substrate is not particularly limited as long as it can form a prepreg, and examples thereof include paper, reinforcing fiber, and the like.

[0082] Examples of paper include linter paper made from cotton and kraft paper made from hardwood.

[0083] Examples of reinforcing fibers include glass fibers, carbon fibers, graphite fibers, aramid fibers, boron fibers, alumina fibers, and silicon carbide fibers. A wide variety of fibers, including but not limited to these, are used. There is no particular restriction or limitation on the form of the reinforcing fibers, and various forms of fibers, including long fibers (unidirectionally stretched), tows, woven fabrics, mats, knits, braids, and short fibers (cut to lengths of less than 10 mm), are used. Here, long fibers refer to single fibers or fiber bundles that are substantially continuous over at least 10 mm. On the other hand, short fibers are fiber bundles cut to lengths of less than 10 mm. For applications requiring high specific strength and specific modulus, a fiber arrangement in which reinforcing fiber bundles are aligned in the same direction is suitable.

[0084] The content of the resin composition in the prepreg is usually 30 to 70 mass%, preferably 35 to 65 mass%, and more preferably 40 to 60 mass%. The content of the base material in the prepreg is usually 30 to 70 mass%, preferably 35 to 65 mass%, and more preferably 40 to 60 mass%.

[0085] The prepreg can be produced by a known method, for example, a sheet molding compound method when the base material is a reinforcing fiber.

[0086] The prepreg can be produced by impregnating a substrate (paper, reinforcing fiber, etc.) with the resin composition. The impregnation method includes a wet method and a hot melt method (dry method). In this case, the viscosity of the resin composition to be impregnated into the substrate is preferably within the above range.

[0087] The wet method is a method in which a substrate (paper, reinforcing fiber, etc.) is immersed in a solution in which a resin composition is dissolved in an organic solvent (methyl ethyl ketone, tetrahydrofuran, methanol, etc.), and then taken out, and the organic solvent is removed by evaporation in an oven or the like to prepare a prepreg.

[0088] The hot melt method is a method in which a resin composition that has been previously made fluid by heating is directly impregnated into a substrate (paper, reinforcing fiber, etc.). Alternatively, in order to use it as a resin film, a method is mentioned in which the resin composition is coated on release paper or the like, the film is then placed on one or both sides of a substrate (paper, reinforcing fiber, etc.) arranged in a flat shape, and then heat and pressure are applied to impregnate the substrate with the resin. By using this hot melt method, a prepreg that is substantially free of residual solvent can be obtained.

[0089] For application of heat and pressure under the prepreg lamination molding method, press molding, autoclave molding, bagging molding, wrapping tape method, internal pressure molding, etc. may be appropriately used.

[0090] Autoclave molding is a process in which prepregs are laid up on a shaped tool plate, then covered with a bagging film, followed by curing by application of heat and pressure while air is pulled out of the laminate. It can allow precise control of fiber orientation and can also provide high quality molded materials with very good mechanical properties by minimizing void content. The pressure applied during the molding process is typically 0.3-1.0 MPa, while the molding temperature is typically in the range of 90-300°C.

[0091] Due to the high Tg of the cured product of the resin composition containing the benzoxazine compound of the present invention, it is advantageous to cure the prepreg at a relatively high temperature (e.g., a temperature of at least 180° C. or at least 200° C.). For example, the molding temperature may be 200-275° C. Alternatively, the prepreg may be molded at a somewhat lower temperature (e.g., 90-200° C.), demolded, and subsequently post-cured at a higher temperature (e.g., 200-275° C.) after removal from the mold.

[0092] The wrapping tape method is a method in which a prepreg is wrapped around a mandrel or some other core to form a tubular fiber reinforced composite. This method can be used in the manufacture of golf shafts, fishing rods, and other rod-shaped products. More specifically, this method involves wrapping a prepreg around a mandrel and wrapping a wrapping tape made of a thermoplastic film over the prepreg under tension in order to fix the prepreg and apply pressure to it. After curing of the resin by heating in an oven, the core is removed to obtain a tubular body. The tension used in wrapping the wrapping tape can be 20-100 N. The molding temperature can be in the range of 80-300°C.

[0093] The internal pressure molding method is a method in which a preform obtained by wrapping a prepreg around a thermoplastic resin tube or some other internal pressure applicator is set inside a metal mold, and then high pressure gas is introduced into the internal pressure applicator to apply pressure, and the metal mold is heated at the same time to mold the prepreg. This method can be used in molding objects with complex shapes such as golf shafts, bats, and tennis or badminton rackets. The pressure applied during the molding process can be 0.1 to 2.0 MPa. The molding temperature can be in the range of room temperature to 300°C, or 180 to 275°C.

[0094] The cured product of the resin composition of the present invention thus obtained and the cured product of the composite (prepreg, etc.) of the present invention are characterized by excellent heat resistance (high glass transition temperature (Tg)), excellent strength (high tensile strength), and easy elongation (relatively small tensile modulus) because they are made from the above-mentioned (1) novolac-type phenolic resin derived from lignin modified with PEG, (2) amine compound, and (3) benzoxazine compound containing a reaction product of an aldehyde compound. Therefore, they are suitably used in a wide range of applications, such as the manufacture of molded products such as electrical parts, automotive parts, building materials, daily necessities, fiber-reinforced composite materials, structural materials, and electrical and electronic materials. EXAMPLES

[0095] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited thereto. <Raw materials> The main raw materials used are as follows: Modified lignin novolac resin 1 (PEG600LN-2; novolac-type phenolic resin derived from lignin modified with polyethylene glycol, modified lignin content 40%, manufactured by the Forestry and Forest Products Research Institute) (see Example 7 of Patent Document 4) Modified lignin novolac resin 2 (PEG400LN-2; novolac-type phenolic resin derived from lignin modified with polyethylene glycol, modified lignin content 40%, manufactured by the Forestry and Forest Products Research Institute) (see Example 4 of Patent Document 4) Phenol novolac resin N1 (Phenolite TD2131, mp 80℃, OH equivalent 103, manufactured by DIC Corporation)

[0096] <Evaluation method> The benzoxazine compounds, prepregs, and cured products obtained as described below were evaluated as follows.

[0097] (1) Softening point and minimum melt viscosity of benzoxazine compounds For the benzoxazine compounds obtained in Examples 1 and 2, and the benzoxazine compound obtained in Comparative Example 3, the endothermic peak temperatures in differential scanning calorimetry (DSC) were measured and taken as softening points (°C). The results are shown in Table 1. In addition, the viscoelasticity of each benzoxazine compound was measured using a 25 mm parallel plate rheometer (MCR300, Anton Paar Japan) under conditions of a gap of 1 mm, a frequency of 1 Hz, a strain of 0.5%, a heating rate of 2°C / min, and a temperature range of 100°C to 180°C, and the minimum melt viscosity (Pa s) was calculated from the obtained viscoelasticity curve. The results are shown in Table 1.

[0098] (2) Solubility test of benzoxazine compounds The benzoxazine compounds obtained in Examples 1 and 2 and the benzoxazine compound obtained in Comparative Example 3 were evaluated for solubility in various solvents shown in Table 2. Specifically, 5 g of solvent was added to 1 g of each benzoxazine compound to dissolve the benzoxazine compound at room temperature (23°C). The resulting mixture was then filtered, and the presence or absence of undissolved matter was visually confirmed. The solubility of each benzoxazine compound in the solvent was evaluated according to the following criteria. The results are shown in Table 2. ○: Completely dissolved (no residue left behind) △: Partially dissolved (some undissolved) ×: Not dissolved at all

[0099] (3) Evaluation of the curing behavior of benzoxazine compounds The curing behavior was evaluated by differential scanning calorimetry (DSC) by heating each benzoxazine compound in a nitrogen atmosphere from room temperature to 300° C. at a heating rate of 10° C. / min to measure the onset temperature and peak temperature of the curing exothermic peak of each benzoxazine compound. The results are shown in Table 3.

[0100] (4) Evaluation of heat resistance of cured product (measurement of glass transition temperature Tg) The glass transition temperatures (Tg) of the cured products obtained in Examples 3 and 4 and the cured products obtained in Comparative Examples 4 and 5 were evaluated based on the peak temperatures of the temperature dispersion curves of the loss tangent (tan δ) obtained from the dynamic viscoelasticity measurements. The dynamic viscoelasticity measurements were performed using Rheogel-E4000 manufactured by UBM Corp. at a frequency of 1 Hz, a heating rate of 2°C / min, and in bending mode. The results are shown in Table 3.

[0101] (5) Evaluation of tensile strength and elastic modulus of the cured product Tensile tests were performed at room temperature at a test speed of 1 mm / min and a gripping distance of 70 mm using rectangular test pieces (length 100 mm, width 10 mm, thickness approximately 5 mm) for the cured products obtained in Examples 3 and 4, and the cured products obtained in Comparative Examples 4 and 5, to measure the tensile strength (MPa) and tensile modulus (GPa). The results are shown in Table 3.

[0102] <Synthesis of benzoxazine compounds> Example 1 In a 300 ml three-necked flask, 15.0 g of modified lignin novolac resin 1 (equivalent weight of phenolic hydroxyl group of resin: 97.5 mmol), 150 g of 4-methyltetrahydropyran, 9.1 g (97.5 mmol) of aniline, and 5.9 g (195 mmol) of paraformaldehyde were charged and stirred at 106 ° C for 3 hours while discharging water from the system using a Dean-Stark apparatus. After that, it was cooled to 80 ° C, insoluble matter was filtered off, and the filtrate was concentrated to obtain 15.1 g of a black solid.

[0103] This black solid 1 The H-NMR spectrum data was as follows: · 1 H-NMR (DMSO-d6) δ / ppm: 6.4-7.2 ppm (benzene ring derived from novolac resin skeleton), 4.5-4.6 ppm (benzoxazine ring methylene), 5.3 ppm (benzoxazine ring methylene), 3.5-3.6 ppm (novolac resin skeleton derived methylene), 3.5 ppm (polyethylene glycol derived methylene) The IR spectrum data of this black solid was as shown in the chart in Figure 1. From this spectrum data, the obtained black solid was identified as a benzoxazine compound. The obtained benzoxazine compounds were evaluated for softening point, minimum melt viscosity, and solubility. The results are shown in Tables 1 and 2.

[0104] Example 2 In a 300 ml three-necked flask, 15.0 g of modified lignin novolac resin 2 (equivalent weight of phenolic hydroxyl group of resin: 97.5 mmol), 150 g of 4-methyltetrahydropyran, 9.1 g (97.5 mmol) of aniline, and 5.9 g (195 mmol) of paraformaldehyde were charged and stirred at 106 ° C for 3 hours while discharging water from the system using a Dean-Stark apparatus. After that, it was cooled to 80 ° C, insoluble matter was filtered off, and the filtrate was concentrated to obtain 15.1 g of a black solid. This black solid 1The H-NMR spectrum data was as follows: · 1 H-NMR (DMSO-d6) δ / ppm: 6.6-7.2 ppm (benzene ring derived from novolac resin skeleton), 4.3-4.6 ppm (benzoxazine ring methylene), 5.3 ppm (benzoxazine ring methylene), 3.2-3.7 ppm (novolac resin skeleton derived methylene), 3.5 ppm (polyethylene glycol derived methylene) From the IR spectrum data of this black solid, the obtained black solid was identified as a benzoxazine compound. The obtained benzoxazine compounds were evaluated for softening point, minimum melt viscosity, and solubility. The results are shown in Tables 1 and 2.

[0105] Comparative Example 1 (Fa-type benzoxazine) Benzoxazine Fa manufactured by Shikoku Chemical Industry Co., Ltd. was used.

[0106] Comparative Example 2 (Phenol Novolac Benzoxazine) In a 2L four-neck flask equipped with a reflux condenser, a thermometer, a dropping funnel, and a stirrer, 4 mol of 37% formaldehyde aqueous solution was added, and 2 mol of aniline was slowly dropped while stirring and cooling to below 10°C in an ice bath. Next, 2 mol of phenol novolac resin N1 was added, and the mixture was reacted by stirring for 6 hours under dioxane reflux conditions, and dried under reduced pressure to obtain phenol novolac benzoxazine (N1-a).

[0107] Comparative Example 3 (Lignin-derived benzoxazine) Herbaceous lignin with an average particle size of about 40 μm was obtained from wastewater generated during the pulp manufacturing process using wheat straw as a raw material. The obtained herbaceous lignin, aniline, and paraformaldehyde were then charged into a reaction vessel in a molar ratio of lignin:aniline:paraformaldehyde = 1:10:20. The reaction vessel was then kept at 100 °C for 30 minutes to obtain benzoxazine derived from herbaceous lignin. The obtained herbaceous lignin-derived benzoxazine compounds were evaluated for softening point, minimum melt viscosity, and solubility. The results are shown in Tables 1 and 2.

[0108] <Preparation of prepreg and cured product> Example 3 A weight of 6.4 g of A4 size paper (paper base phenolic resin craft paper, thickness about 0.23 mm) was measured. The benzoxazine compound obtained in Example 1 was weighed to the same weight as the paper and dissolved in 30 ml of tetrahydrofuran. The tetrahydrofuran solution was then completely impregnated into the paper and dried at 50°C for 24 hours to produce a prepreg containing about 50% of the benzoxazine compound. The obtained prepreg was sandwiched between hot plates in an oven and heated at 150°C for 4 hours and at 200°C for 2 hours to obtain a cured product. The heat resistance and mechanical properties of the resulting cured product were evaluated, and the results are shown in Table 3.

[0109] Example 4 A prepreg and a cured product containing about 50% benzoxazine were obtained in the same manner as in Example 3, except that the benzoxazine compound obtained in Example 2 was used. The heat resistance and mechanical properties of the resulting cured product were evaluated, and the results are shown in Table 3.

[0110] Comparative Example 4 A prepreg and a cured product were obtained in the same manner as in Example 3, except that the conventional monomer-type benzoxazine compound (Fa-type benzoxazine) of Comparative Example 1 was used instead of the benzoxazine compound obtained in Example 1. The heat resistance and mechanical properties of the resulting cured product were evaluated, and the results are shown in Table 3.

[0111] Comparative Example 5 A prepreg and a cured product were obtained in the same manner as in Example 3, except that the conventional phenol novolac benzoxazine compound (N1-a) of Comparative Example 2 was used instead of the benzoxazine compound obtained in Example 1. The heat resistance and mechanical properties of the resulting cured product were evaluated, and the results are shown in Table 3.

[0112] Comparative Example 6 An attempt was made to prepare a prepreg in the same manner as in Example 3, except that the benzoxazine compound (non-PEG chain) derived from herbaceous lignin in Comparative Example 3 was used instead of the benzoxazine compound obtained in Example 1. However, the compound was unable to dissolve in tetrahydrofuran and other solvents, and it was impossible to prepare a prepreg. [Table 1] [Table 2] [Table 3]

[0113] From Table 1, it was confirmed that the benzoxazine compounds of the present invention obtained in Examples 1 and 2 have softening points, the softening points are low, and the minimum melt viscosity is also small. Therefore, the present benzoxazine compounds are applicable to the formation of prepregs, casting processes, etc. In contrast, the conventional benzoxazine compound of Comparative Example 3 (corresponding to the lignin-modified benzoxazine compound of Patent Document 2) does not have a softening point. Therefore, it is not applicable to the formation of prepregs, casting processes, etc.

[0114] As seen from Table 2, the benzoxazine compounds of the present invention obtained in Examples 1 and 2 had high solubility in various organic solvents, whereas the benzoxazine compound of Comparative Example 3 was insoluble in any organic solvent.

[0115] From Table 3, it was confirmed that the benzoxazine compounds of the present invention obtained in Examples 1 and 2 have lower DSC peak onset temperatures and DSC peak temperatures than the monomer-type benzoxazine compound of Comparative Example 1 (Fa-type benzoxazine) and the phenol novolac-type benzoxazine compound (N1-a) of Comparative Example 2, and therefore the curing reaction starts and completes in the low temperature range.

[0116] From Table 3, it was confirmed that the cured products obtained in Examples 3 and 4 had significantly higher glass transition temperatures and superior heat resistance than the cured products obtained in Comparative Examples 4 and 5.

[0117] From Table 3, it was confirmed that the cured products obtained in Examples 3 and 4 had higher tensile strength and lower tensile modulus than the cured products obtained in Comparative Examples 4 and 5. [Industrial Applicability]

[0118] The benzoxazine compound of the present invention has high solubility and meltability in organic solvents. In addition, the cured product obtained by curing the resin composition containing the benzoxazine compound of the present invention has the characteristics of excellent heat resistance (high glass transition temperature (Tg)), excellent strength (high tensile strength), and easy elongation (relatively small tensile modulus). Therefore, it is suitable for use in molded products obtained by forming prepregs, etc.

Claims

1. A benzoxazine compound comprising a reaction product of a novolac-type phenolic resin derived from lignin modified with polyethylene glycol, an amine compound, and an aldehyde compound.

2. 2. The benzoxazine compound according to claim 1, wherein the novolac phenolic resin is obtained by reacting lignin modified with polyethylene glycol, a phenolic resin, and an aldehyde compound.

3. A resin composition comprising the benzoxazine compound according to claim 1 or 2.

4. A cured product of the resin composition according to claim 3.

5. A composite comprising the resin composition according to claim 3 and a substrate.

6. A prepreg comprising the resin composition according to claim 3 and a substrate.

7. A cured product of the composite according to claim 5.

8. A method for producing a benzoxazine compound, comprising the steps of: (1) a step of reacting lignin modified with polyethylene glycol with a phenolic resin and an aldehyde compound to obtain a novolac-type phenolic resin; and (2) A step of reacting the novolak-type phenolic resin obtained in (1) above, an amine compound, and an aldehyde compound to obtain a benzoxazine compound. A manufacturing method comprising:

Citation Information

Patent Citations

  • Lignin type benzooxazine and preparation method thereof

    CN109265633A

  • Bio-based degradable benzoxazine resin, and preparation method, cured resin, compound and degradation method thereof

    CN112442158A

  • Polyethylene glycol modified benzoxazine compound with different phenol types and preparation method of compound

    CN113501922A

  • JP1974047378A

  • Excitation control system

    JP1981071430A

Cited By

  • Preparation method of high-carbon / high-alloy composite brake disc for racing car

    CN120737537A